Bottom boundary layer in the Black Sea: Experimental data, turbulent diffusion, and fluxes. - Kushnir, V M (PANGAEA, 2007)
Measurements of 14 vertical profiles of currents and hydrological parameters in the near-bottom layer with depth resolution of 0.1 m were carried out in several regions of the Black Sea shelf, at five points over the continental slope, and in three deep water regions. The upper boundary of the benthic boundary layer (BBL) was reliably determined at a point at distance from 5-7 to 35-40 m from the bottom where the gradients of density and current velocity changed. Experimental data obtained were used to determine the coefficient of bottom friction, friction velocity, coefficients of vertical diffusion of momentum and density, and vertical fluxes of temperature and salinity in the BBL.
(Table 1) Conditions of vertical near-bottom profiling and the main parameters of the benthic boundary layer in several regions of the Black Sea shelf
Keywords: Angle; Archive of Ocean Data; ARCOD; Black Sea; Brunt-Väisälä frequency; Current speed; Dynamical Richardson number; Hydrophysical profiler, OLT-D type; Hydrophysical profiler OLT-D; OLT-14; OLT-15; OLT-16; OLT-19; OLT-21; OLT-28; OLT-30; OLT-31; OLT-32; OLT-49; OLT-50; OLT-55; OLT-69; OLT-7; OLT-71; OLT-72; OLT-73; OLT-74; OLT-77; OLT-78; OLT-85; OLT-D; OLT-P1